Effect of cornstarch partial substitution by millet flour and agro-industrial by-products on the development of gluten-free doughs - Karen F. Irigoytia; Carolina E. Genevois; Marina F. de Escalada Pla (Future Foods)
Agro-industrial by-products such as rice bran (RB) and soybean extruded-expelled meal (SEE), along with millet, contain nutrients that should be integrated to food-chain. The aim of this study was to characterise these raw-materials and evaluate their effect in the development of gluten-free doughs. A factorial design was used to evaluate the substitution of cornstarch up to 60 % by RB, SEE and millet flour. RB and SEE contain 31.5 and 21 % dietary fibre (DF); 17.2 and 8.8 % lipids; 13.1 and 45.9 % protein; respectively. Millet flour presented 9.2 % protein, 6.3 % lipids and 5.3 % DF. Surfaces areas of particles from RB and SEE were higher (63 and 94 m2/kg, respectively) than those from millet flour (25m2/kg). All these properties modified dough hydration, affecting the optimal fermentation time of dough as well as pasting properties. The minimum cornstarch substitution presented the highest peak viscosity (1750cP) and longer optimal fermentation time (53 min). While system 4, with the maximum cornstarch substitution by 30 % of RB, 15 % of SEE and 15 % millet, tended to the lowest setback value (134cP). Significant positive correlations among dough pasting properties and fermentation parameters were recorded. Partial substitution of cornstarch by RB, SEE and millet enhanced doughs development.